Problematika Pendidikan Agama Islam di Daerah 3T (Terluar, Tertinggal, dan Terdepan) - Munawir; Nizar Ibrahim, Muhamad; Islamiah, Rahmatul (Universitas Majalengka, 2024)
Islamic religious education in the 3T region experiences various challenges, which affect ease of access, quality and relevance of Islamic religious learning. These areas are often neglected in infrastructure development, including educational infrastructure, resulting in limited access for their residents. In addition, a shortage of qualified teaching staff and limited learning materials are serious obstacles to providing quality Islamic religious education in the region. Unstable social and economic conditions also complicate the situation, reducing the availability of human resources who can become qualified Islamic religious teachers. This research aims to dig deeper into the problems of Islamic religious education in the 3T area. This research uses a literature study research method (Literature Reviev) which relies on library sources from books and articles in scientific journals related to the topic of discussion. The research results highlight several problems, such as limited learning materials that suit local needs, a lack of number and quality of teachers, and a lack of facilities that support learning. Social and economic instability is also a factor that influences the effectiveness of Islamic religious education in the 3T region.